2020
DOI: 10.12965/jer.2040270.135
|View full text |Cite
|
Sign up to set email alerts
|

Gross motor function and health fitness in adults with autistic spectrum disorder and intellectual disability: single-blind retrospective trial

Abstract: This study aimed at providing an exercise program for each type of disability after analyzing the exercise program performed by adults with intellectual disability (ID) or autistic spectrum disorder (ASD). Twentynine male adults voluntarily took part in this study, whose age ranged from 19 to 28 years and with an average body mass index of 23.98± 4.02 kg/m 2. The sample was divided into two groups as follows: ASD group (ASDG; n= 15) and ID group (IDG, n= 14). The selected tests used to measure gross motor func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Only 4 of the 22 studies reviewed (i.e. ~18%) (Barwick et al, 2012; Cha et al, 2020; Todd et al, 2019; Yu & Jee, 2020), 2 of which were by the same research group (Cha et al, 2020; Yu & Jee, 2020), were restricted to purely the age group of our interest (Table 1). Specifically, Yu and colleagues assessed the effects of an educational play program involving games such as tug-of-war and chasing, as well as sport-specific training involving floorball, basketball, inline skating, and jumping activities on PF and GMF in young adults with ASD between 20 and 29 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 4 of the 22 studies reviewed (i.e. ~18%) (Barwick et al, 2012; Cha et al, 2020; Todd et al, 2019; Yu & Jee, 2020), 2 of which were by the same research group (Cha et al, 2020; Yu & Jee, 2020), were restricted to purely the age group of our interest (Table 1). Specifically, Yu and colleagues assessed the effects of an educational play program involving games such as tug-of-war and chasing, as well as sport-specific training involving floorball, basketball, inline skating, and jumping activities on PF and GMF in young adults with ASD between 20 and 29 years.…”
Section: Resultsmentioning
confidence: 99%
“…Of the two studies that did not find statistically significant results, one study reported that there were no significant changes in skeletal muscle mass following training involving strength and endurance exercises, nutrition education, and coaching for stress reduction (Spratt et al, 2018). The other study did not find any significant differences in PF measures between ASD and intellectual disability (ID) groups following a PA program; however, the study assessed outcomes at only one time-point, thereby precluding any conclusions to be drawn regarding within-group improvements in the ASD group (Cha et al, 2020) (see Table 4).…”
Section: Pf and Pa Engagementmentioning
confidence: 98%
“…However, activities such as jogging, may not require extensive procedures for teaching. Indeed, several common procedures and strategies emerged across studies (Cha et al, 2020). First, embedding exercise into age-appropriate activities and games may increase motivation to engage in exercise, similar to the program used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This study used the GMF scale-II (Cha et al, 2020). This allows the instructor to accurately and quickly measure any delays in underlying motion patterns of the participants compared to their peers.…”
Section: Measurement Of Gmfmentioning
confidence: 99%
“…Compared to formerly described test setups for adult patients without CF [21,39], the implementation of our test Results are presented as mean ± standard deviation ðSDÞ. n: number of patients with complete data sets.…”
Section: Pulmonary Medicinementioning
confidence: 99%